Roughage levels and comparison of mixed rations vs self-feeders in whole shelled corn finishing programs - C.T. Milton; Robert T. Brandt Jr.; S.A. Shuey (Kansas Agricultural Experiment Station Research Reports, 1994)
Two trials were conducted to evaluate roughage levels in whole shelled-corn finishing diets and to compare use of self-feeders to a total mixed ration in a whole corn program. In trial 1, steers were fed whole corn diets alone or with 4 or 8% roughage or a rolled corn diet with 8% roughage. Increasing the roughage level increased dry matter in take, feed required per unit of gain, and carcass weight and finish, and reduced the incidence of liver abscesses. Despite better feed efficiency and lower costs of gain, reducing the dietary roughage level reduced profitability because of lighter slaughter weights. In trial 2, feeding 4% vs no roughage in a whole-corn finishing program increased dry matter intake and tended to increase rate of gain by finishing heifers. No performance benefit resulted from feeding a total mixed ration vs using self-feeders and providing chopped hay in a feed bunk. Feeding very little or no roughage in whole corn diets can improve feed efficiency and reduce cost of gain. However, these advantages can be outweighed by potentially lower slaughter weights and increased metabolic problems (acidosis, bloat, liver abscesses).
Keywords: Cattlemen& #x27; s Day; 1994; Kansas Agricultural Experiment Station contribution; no. 94-373-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 704; Beef; Whole shelled corn; Roughage level; Feedlot